2021
DOI: 10.9734/ajrcs/2021/v6i430124
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plant Population and NPS Fertilizer Rates on Yield and Yield Components of Mung Bean (Vigna radiata L. Wilczek) in Bako, Western Ethiopia

Abstract: Mung bean (Vigna radiata L.) is a pulse crop with multiple uses and it was introduced recently in the study area. However, its productivity is limited by inadequate plant population and NPS fertilizer rate in the study area. Hence, this study was carried out to determine optimum plant population and NPS fertilizer rates for mung bean borda varaity in Bako, Western Ethiopia. The experiment comprised of factorial combinations of four different plant populations (500000, 571429, 666667, and 800000 plants ha-1) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 2 publications
0
0
0
Order By: Relevance
“…Whereas the lowest plant height was observed in S3F2 (40.37 and 44.53 cm) at 45 and 60 DAS. Plant height might be varied in different crops due to plant spacing; similar findings were also reported by Sefera et al (2021) in mungbean. On the other hand, combination of organic and inorganic fertilizers was created better plant height in groundnut (Mohanty et al, 2022;El-sherbeny et al, 2023) and in green gram (Rajendar et al, 2021) than only inorganic fertilizers application.…”
Section: Plant Heightsupporting
confidence: 76%
See 3 more Smart Citations
“…Whereas the lowest plant height was observed in S3F2 (40.37 and 44.53 cm) at 45 and 60 DAS. Plant height might be varied in different crops due to plant spacing; similar findings were also reported by Sefera et al (2021) in mungbean. On the other hand, combination of organic and inorganic fertilizers was created better plant height in groundnut (Mohanty et al, 2022;El-sherbeny et al, 2023) and in green gram (Rajendar et al, 2021) than only inorganic fertilizers application.…”
Section: Plant Heightsupporting
confidence: 76%
“…It was also showed that maximum number of branches plant -1 at 30, 45 and 60 DAS was recorded in S1F0 (0.20), S3F0 (2.27) and S3F5 (2.70) whereas minimum number of branches plant -1 S3F3 (0.00), S1F1 (0.33 and 0.87) treatment combinations respectively (Table 3). Similar results corroborated that the plant spacing increases the number of branches plant -1 (Taufiq and Kristiono 2016;Sefera et al, 2021).On the other hand, the application of different fertilizer doses the number of branches have been changed (Achakzai et al, 2012;Mohanty et al, 2022).…”
Section: Number Of Branchessupporting
confidence: 52%
See 2 more Smart Citations